Facilitating the Access and Use of CSA and CIS Course Modules in African Higher Education Systems - Nimusiima, Alex; Nakayiwa, Florence Mayega; Majaliwa, Jackson Gilbert Mwanjalolo (2024)
To facilitate the access and use of CIS/CSA curricula developed by RUFORUM/WASCAL, the cluster has organised a side event during the RUFORUM Triennial Conference 2024 to create awareness of training curricula developed by the AICCRA project among university leaders, lecturers and students with a view of mainstreaming the developed CSA and CIS curricular in the training programmes of universities. This deliverable reports the outcomes of the event, especially the mainstreaming of the CIS/CSA course modules in a University in Tanzania and a request from 22 universities in 13 African countries, including 11 non-AICCRA countries